2021
DOI: 10.1002/ppul.25627
|View full text |Cite
|
Sign up to set email alerts
|

Review of CFTR modulators 2020

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) modulators are small molecules that directly impact the CFTR protein, improving the function of the CFTR chloride and bicarbonate channel. Beginning in 2012 with the Food and Drug Administration approval of the first CFTR modulator, ivacaftor, this class of medications has had largely positive effects on many outcomes in people with cystic fibrosis (PwCF), including lung function, growth, and other clinical parameters. There have been continued excitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 68 publications
(162 reference statements)
0
27
0
Order By: Relevance
“…4 It has been shown that ivacaftor, lumacaftor, and tezacaftor (used singly or in combination) are safe and efficacious in children aged 6-11 years. 5 Furthermore, the results of a 24-week, Phase-III open-label trial of ETI have shown that the treatment was as safe and effective in CF patients aged 6-11 years with at least one F508del allele as in adults and adolescents. 6 However, as is usual in clinical trials, this study excluded patients with severe pulmonary impairment (defined as an FEV 1 of <40% of the predicted value).…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been shown that ivacaftor, lumacaftor, and tezacaftor (used singly or in combination) are safe and efficacious in children aged 6-11 years. 5 Furthermore, the results of a 24-week, Phase-III open-label trial of ETI have shown that the treatment was as safe and effective in CF patients aged 6-11 years with at least one F508del allele as in adults and adolescents. 6 However, as is usual in clinical trials, this study excluded patients with severe pulmonary impairment (defined as an FEV 1 of <40% of the predicted value).…”
Section: Introductionmentioning
confidence: 99%
“…CFTR modulators are clearly of value to a large number of people with CF, and quality of life parameters such as CFQ-R has been shown to improve in patients given CFTR modulators in trials. 3 Furthermore, there are reports of benefit from ivacaftor use for non-pulmonary manifestations such as pancreatitis. 8 Our patient had significant benefit with use of ivacaftor, with marked improvement in non-respiratory symptoms and subsequent quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…1 The diagnosis of CF can be challenging for those who do not have typical symptoms, and this can raise issues about how they should be managed and whether it is appropriate to use CFTR modulators. 2,3 There are a number of mutations known to cause a variable phenotype, in particular the CFTR exon 4 Arg117His mutation. 2,4 This mutation exhibits reduced channel conductivity compared with wild type CFTR.…”
Section: Introductionmentioning
confidence: 99%
“…CFTR modulators are drugs that act by improving production, intracellular processing, and/or function of the defective CFTR protein. The management may include two correctors and a potentiator (e.g., elexacaftor-tezacaftor-ivacaftor) to restore the function of the mutant CFTR protein more fully [ 37 ]. CFTR modulators may prevent lung damage or improve lung function but there is no evidence supporting reversal of already damaged bronchi, suggesting that CF patients with structural damage will continue to be high risk for pulmonary NTM.…”
Section: Methodsmentioning
confidence: 99%